BB84 with Both Several Cloning and Intercept-resend Attacks - Mustapha Dehmani; El Mehdi Salmani; Hamid Ez-Zahraouy; Abdelilah Benyoussef (International Journal of Electrical and Computer Engineering (IJECE), 2018)
The goal of the protocol QKD BB84 is to allow a transmitter and a receiver which uses a quantum channel to exchange their keys and to detect the presence of eavesdropping attacks. In the present research, we investigate the effect of several eavesdroppers with both intercept-resend and cloning attacks. We will propose the different possible cases of the positioning of the eavesdroppers and their strategies of attacks; also we will calculate the mutual information for each case. The explicit expressions of the mutual information and quantum error clearly show that the security of the exchanged information depends on the numbers of the eavesdroppers and their attacks parameters on the quantum channel.